(2+4y)-(y+9)=20

Simple and best practice solution for (2+4y)-(y+9)=20 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2+4y)-(y+9)=20 equation:


Simplifying
(2 + 4y) + -1(y + 9) = 20

Remove parenthesis around (2 + 4y)
2 + 4y + -1(y + 9) = 20

Reorder the terms:
2 + 4y + -1(9 + y) = 20
2 + 4y + (9 * -1 + y * -1) = 20
2 + 4y + (-9 + -1y) = 20

Reorder the terms:
2 + -9 + 4y + -1y = 20

Combine like terms: 2 + -9 = -7
-7 + 4y + -1y = 20

Combine like terms: 4y + -1y = 3y
-7 + 3y = 20

Solving
-7 + 3y = 20

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + 3y = 20 + 7

Combine like terms: -7 + 7 = 0
0 + 3y = 20 + 7
3y = 20 + 7

Combine like terms: 20 + 7 = 27
3y = 27

Divide each side by '3'.
y = 9

Simplifying
y = 9

See similar equations:

| .12y+0.06(y+2000)=1020 | | 2x+90+90+x=360 | | 0.5(0.5y-0.5)= | | 20x+12=172 | | 8x-5x=5x-2 | | 8(10n-10)+3= | | 1/2(30)(36) | | 7x-6(5x+3)=-156 | | 3x-9x+18=18x | | c/2+4=6 | | w^2+2wp-35p^2=0 | | n+33/2=57/9 | | -2(3x+1)=3(4x+1) | | -2n+12=54 | | 2(3+2x)=-6 | | -5(7-5r)=19-2r | | 6/7x-1/4x+10-11/14x | | -4y+10=-3+10y | | x+1/x-2=4/7 | | 0.6666667a-0.75=0.75a | | 3m=20-2m | | 4p-3p= | | a+13=2a-7 | | (x+2)(X+-1)(x+2i)=0 | | -2(a-8)=16-a | | -4x=-50-2 | | 5x+2(3-x)+1=11 | | -6y+4(y+5)=36 | | 1/6p=1/3 | | -6x=6(1-x) | | -6x^6-18x^5+60x^4=0 | | x*4=x*4 |

Equations solver categories